2017
DOI: 10.1098/rsfs.2016.0114
|View full text |Cite
|
Sign up to set email alerts
|

Competition brings out the best: modelling the frustration between curvature energy and chain stretching energy of lyotropic liquid crystals in bicontinuous cubic phases

Abstract: It is commonly considered that the frustration between the curvature energy and the chain stretching energy plays an important role in the formation of lyotropic liquid crystals in bicontinuous cubic phases. Theoretic and numeric calculations were performed for two extreme cases: parallel surfaces eliminate the variance of the chain length; constant mean curvature surfaces eliminate the variance of the mean curvature. We have implemented a model with Brakke's Surface Evolver which allows a competition between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…This medial surface (or axis) is a geometric construction that produces a centred skeleton of the original shape (see [46] for a recent review). For the case of bicontinuous structures, it represents a generalized line graph that also provides a robust definition of local domain (or channel) size and hence relates to questions of chain stretching frustration and geometric homogeneity [44,47,48,49]. For an object defined by its bounding surface, for every surface point p with surface normal vector n( p), the corresponding medial surface point is defined as p þ d( p) .…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 7: 20160161mentioning
confidence: 99%
“…This medial surface (or axis) is a geometric construction that produces a centred skeleton of the original shape (see [46] for a recent review). For the case of bicontinuous structures, it represents a generalized line graph that also provides a robust definition of local domain (or channel) size and hence relates to questions of chain stretching frustration and geometric homogeneity [44,47,48,49]. For an object defined by its bounding surface, for every surface point p with surface normal vector n( p), the corresponding medial surface point is defined as p þ d( p) .…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 7: 20160161mentioning
confidence: 99%
“…terminal boundaries lie along the medial set). As medial geometry encodes the shortest distance to the "center" of a complex morphology, previous studies have proposed that medial thickness can be used as a heuristic measure of packing frustration [17,20,35] or otherwise an ingredient in phenomenological models of its costs [37] in TPN morphologies. We next exploit a fully molecular description of TPN assembly, the SST of BCP melts, to test and establish the direct connections between the medial geometry of complex TPN, the underlying configurations of molecular constituents and the thermodynamic stability of the DG phase.…”
Section: Medial Anatomy Of Tpn Morphologiesmentioning
confidence: 99%
“…The results confirmed that the G surface is the most stable structure among the hyperbolic surface categories, followed by D and P surface structures. A recent publication indicated that bicontinuous phases are determined by the competition and compromise between the CMC and parallel surface models [150].…”
Section: Structure and Formation Mechanismmentioning
confidence: 99%